POTENSI DAN TINGKAT PEMANFAATAN SUMBERDAYA IKAN DEMERSAL DI PERAIRAN KABUPATEN PEKALONGAN - Andriani, Novita Lusi; NND, Dian Ayunita (9-772301-994005, 2012)
Pekalongan Regency seawaters is one of potential demersal fish distribution area. If resources utilization are uncontrol, the resources will be threatened by fishing effort increase. Information about potency and utilization rate should be known. This research purposes were to analyze potency of demersal fish, biological and economic aspects of demersal fish utilization in Pekalongan Regency seawaters that analyzed Catch per Unit Effort (CPUE), Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), dan Open Access Equilibrium (OAE).This research conducted in Februari-April 2011. Research method was explorative survey. Sampling method was using purposive sampling with 36 samples obtained. Data that used in this research were primary and secondary data. Data analysis method used swept area and bioeconomic method â Gordon-Schaefer Model.This study showed that the demersal fish potency in Pekalongan Regency Seawaters was 36.16 metric tons. The average Catch per Unit Effort (CPUE) rate for 2001-2010 in Pekalongan Regency Seawaters was 0,055 metric tons/trip. The optimum catch (Copt) of the Maximum Sustainable Yield (MSY) was 880 metric tons per year with optimum effort (Eopt) 17.237 trip per year. The optimum catch (Copt) of the Maximum Economic Yield (MEY) was 735 metric tons per year with optimum effort (Eopt) was 10.236 trip per year. The optimum catch (Copt) of the Open Access Equilibrium (OAE) was 849 metric tons per year with optimum effort (Eopt) was 20.472 trip per year. The demersal fish resource utilization rate during the last 10 years in Pekalongan Regency has an average rating of 117%, which means that the demersal fish resource utilization rate was overfishing.